Analysis of EZproxy server logs to visualise research activity in Curtin’s online library - Joseph, Pauline; Kent, Aaron J.; Green, Peter; Robinson, Matthew; Bellenger, Amanda (EMERALD GROUP PUBLISHING LTD, 2019)
© 2019, Emerald Publishing Limited. Purpose: The purpose of this paper is to develop data visualisation proof of concept prototypes that will enable the Curtin University Library team to explore its users’ information-seeking behaviour and collection use online by analysing the library’s EZproxy logs. Design/methodology/approach: Curtin Library’s EZproxy log file data from 2013 to 2017 is used to develop the data visualisation prototypes using Unity3D software. Findings: Two visualisation prototypes from the EZproxy data set are developed. The first, “Global Visualisation of Curtin Research Activity”, uses a geographical map of the world as a platform to show where each research request comes from, the time each is made and the file size of the request. The second prototype, “Database Usage Visualisation”, shows the use of the library’s various subscription databases by staff and students daily, over a month in April 2017. Research limitations/implications: The paper has following limitations: working to a tight timeline of ten weeks; time taken to cleanse noise data; and requirements for storing and hosting the voluminous data sets. Practical implications: The prototypes provide visual evidence of the use of Curtin Library’s digital resources at any time and from anywhere by its users, demonstrating the demand for the library’s online service offerings. These prototype evidence-based data visualisations empower the library to communicate in a compelling and interesting way how its services and subscriptions support Curtin University’s missions. Originality/value: The paper provides innovative approaches to create immersive 3D data visualisation prototypes to make sense of complex EZproxy data sets.